Conceptual, Traditional And New Media Training Needs: A Study of County Extension Agent Perceptions - Clifford W. Scherer; Steve Masiclat (Journal of Applied Communications, 1988)
This study examines the extent to which county Extension agents perceive their need lor training in three broad areas-traditional media, new media, and conceptual areas. While the impact of the new communication technologies on Extension's internal information delivery system has been dramatic, Extension's publics also are reacting to changes in other delivery systems such as cable'television, computers, and VCRs. The changing information environment in which agents currently operate suggests that our traditional communication training efforts may need to be modified. This study found that agents appear to be aware of these changing needs, and rank the need for traditional media training considerably lower than their perceived need for communication training in either new media such as desktop publishing, or conceptual areas such as communication planning and strategies.